T cell immunodeficiency in dyskeratosis congenita. Issue 4 (April 1992) - Lee, B W; Yap, H K; Quah, T C; Chong, A; Seah, C C
Abstract : Dyskeratosis congenita has been found to be associated with abnormal immune function. In this study we report a patient with this association. He developed Pneumocystis carinii interstitial pneumonia, and impaired cell mediated immunity was confirmed by the presence of depressed lymphoproliferative responses to in vitro stimulation with mitogen. Enumeration of T cell subsets showed a severely depressed CD4:CD8 ratio (0.38), which is the likely cause for impaired cell mediated immunity. The T cell activation pathway appeared intact, as his T lymphocytes were able to express activation markers (CD25 and HLA-DR) after mitogen stimulation.